Meneguhkan Adab Santri di Era Digital: Kajian Spiritual Pembinaan Akhlak dalam Tradisi Pesantren - Aida Naja Sabiela; Nasrulloh (Al-Kindi, 2026)
This study is based on developments in digital technology that require Islamic boarding schools to reaffirm the value of manners as the foundation for fostering student’s character. Although digitization has changed learning patterns and interactions, the traditions of Islamic boarding schools remain relevant as moral guides that shape simplicity, discipline, humility, independence, and respect for religious teachers. The integration of adab values with technology means that digital devices are not a threat, but a means of strengthening learning as long as their use is guided by Islamic ethics. Thus, santri are expected to become digitally competent individuals who remain moral in the face of modern challenges. This study uses a qualitative approach with a literature review of relevant books, journal articles, and scientific work. The focus of the research is to analyze the concept and implementation of santri manners in the digital era, including spiritual guidance through obedience to kiai, discipline in worship, simple living, honesty, and media ethics. The study also examines how Islamic boarding schools integrate manners with technology through digital literacy, the use of modern learning media, and the formation of santri as moral agents in cyberspace. The results of the study show that adab values remain the main foundation of pesantren education. Pesantren are able to strengthen the character of santri through digital literacy programs, media ethics, and cyber dakwah, so that santri not only master digital skills but are also able to maintain Islamic adab and ethics in every digital activity.